Hubungan Tingkat Pengetahuan Mahasiswa terhadap Sikap Memilih Antioksidan sebagai Anti-Aging di Fakultas Kedokteran Universitas Muhammadiyah Semarang - Oktavia Nurul Khotimah; Eko Krisnarto; Afiana Rohmani (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Purchases of beauty products by around 126,8 million individuals were, dominatedly by Indonesian teenagers. This increasing precentage of beauty product users raisers concerns regarding inappropriate product selection. Nadequate attention to skin conditions, and environmental influences. These factors may not lead to healthy and radiant skin but could instead contribute to various skin problems. This study aims to analyze the relationship between the knowledge level of university students and their and attitudes toward selecting antioxidants as Anti-Aging agents. This study employs observational analytical design with a cross sectional aproach. The sample consists of 260 students, inrolled in the year 2023 and 2024 cohorts. At the Faculty of Medicine, University of Muhammadiyah Semarang. Participants were selected using purposive sampling method based on inclusion criteria which required them to be actively attending lectures. Data were collected on gender, age, knowledge level and attitude toward antioxidant selection. These variables were measured using a structured questionnaire, and the relationship between variables were analyzed using statistical test Rank Spearman. The majority of respondents 83,5 % (n = 217) demonstrated a high level of knowledge, while 91.9% (n = 239) exhibited a positive attitude toward selecting antioxidants as Anti-Aging agents. The Spearman Rank correlation test revealed a significant relationship between knowledge level and attitude, with a p-value of 0.000, and a correlation coefficient ( r ) 0.562. There was a significant relationship between the level of knowledge and the attitude toward choosing antioxidants as Anti-Aging agents among Students of the Faculty of Medicine University of Muhammadiyah Semarang.